Efektivitas Teknik Relaksasi Napas dalam Terhadap Penurunan Sesak Napas pada Pasien Asma : Narrative Literatur - Elsa Devina Seftiani; Agisni Fatihaturrohmah; Nadia Mawaddah; Septiyani Ayusita Aprilia; Faiza Zahra Amelia; Popi Sopiah (Pusat Riset dan Inovasi Nasional, 2026)
Asthma is a chronic inflammatory disease of the respiratory tract characterised by symptoms such as difficulty breathing, coughing, and wheezing, which can affect the quality of life of individuals who experience it. In addition to medical treatment, non-medical approaches such as relaxation breathing techniques have been widely used to reduce breathing difficulties and improve lung function. This study is a literature review that aims to assess the effectiveness of deep breathing techniques, such as slow deep breathing, diaphragmatic breathing, and pursed-lip breathing, in reducing breathing difficulties in asthma patients. Data were collected through a search of articles on Google Scholar, Semantic Scholar, and Crossref with a publication range from 2015 to 2025. Of the total 423 articles found, 10 articles met the inclusion criteria and were analysed further. The results of this study show that deep breathing techniques can increase oxygen saturation, reduce breathing frequency, and improve lung ventilation. This approach also contributes to reducing perceived symptoms and improving asthma control, making it a safe and easy-to-apply complementary therapy. However, variations in study design, number of respondents, and duration of intervention are challenges that need to be addressed. Further research with stronger methods and standardised guidelines is needed so that this technique can be properly integrated into asthma management.